Pengaruh Burnout Terhadap Kinerja Perawat di Instalasi Intensive Care RSUD Kardinah Tegal - Astiti, Indita Wilujeng; wati, Etlida (Jurnal Keperawatan Muhammadiyah, 2020)
Objective: to identify the relation of burnout on nursing performance of nurse in intensive care instalation RSUD Kardinah tegalMethods: this articleÂ is a quantitative study with a cross-sectional approach, usedÂ total sampling technique with 51 respondents. Data were analyzed with the Spearman-rho correlation test.Results: This study shows that there is a relations between burnout and nurse performance in providing nursing services with a p-value of 0.004.Conclusion: The results showed that the average level of burnout was mild and moderate, while the average respondent had a level of performance that was quite good and good.